2021
DOI: 10.1111/jfbc.13671
|View full text |Cite
|
Sign up to set email alerts
|

High‐fat diet and fructose drink introduced after weaning rats, induces a better human obesity model than very high‐fat diet

Abstract: In the present study, we associated a high-fat diet (HF group: 45% kcal from lipids) or very high-fat (VHF group: 60% kcal from lipids) diet with a fructose drink (10% fructose) for hydration. Normal rat chow that received the control diet (content 16.3% kcal from lipid-AIN93G) and water. The treatments were introduced soon after weaning and were administered for 70 days. We aimed to compare HF and VHF groups and find which acts as a better model mimicking human obesity. Body mass gain, final body weight, adip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 48 publications
(58 reference statements)
0
1
0
Order By: Relevance
“…Studies in rodents have shown that high‐fat diets can provide striking characteristics of human obesity, such as hyperphagia, accumulation of abdominal adipose tissue, development of NAFLD, cardiovascular diseases, and impairments in bone formation (Alsina et al, 2016; de Souza et al, 2021; Harrat et al, 2019; Natal & Ribeiro, 2016). It is noteworthy that all these effects seem to be more damaging when using a high‐fat diet, reaching more than 60% of this macronutrient (Kolahdouzi et al, 2019; Lima et al, 2021; O'Neill & Raggi, 2020; Parry & Hodson, 2017; Retterstøl et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Studies in rodents have shown that high‐fat diets can provide striking characteristics of human obesity, such as hyperphagia, accumulation of abdominal adipose tissue, development of NAFLD, cardiovascular diseases, and impairments in bone formation (Alsina et al, 2016; de Souza et al, 2021; Harrat et al, 2019; Natal & Ribeiro, 2016). It is noteworthy that all these effects seem to be more damaging when using a high‐fat diet, reaching more than 60% of this macronutrient (Kolahdouzi et al, 2019; Lima et al, 2021; O'Neill & Raggi, 2020; Parry & Hodson, 2017; Retterstøl et al, 2018).…”
Section: Introductionmentioning
confidence: 99%